Character Education Based on the Book Mau'idhotul Mukminin in Fostering the Spirit of Entrepreneurship among Students of the Fathul Ulum Islamic Boarding School in Diwek - Habibi, Achmad; Arifin, Imron (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study examines the implementation of character education based on the Mau'idhotul Mukminin book to foster the entrepreneurial spirit of students at Pesantren Fathul Ulum, Jombang. Written by Sheikh Jamaluddin al-Qasimi, this book serves as a reference for instilling Islamic values in entrepreneurship, such as ethics in work and business conduct. Using a qualitative approach, data were collected through observations, interviews, and documentation. Pesantren Fathul Ulum integrates Islamic education rooted in classical texts with entrepreneurship training in agriculture, livestock farming, and garment production. The findings reveal that this approach effectively develops students' character to be religious, independent, and adaptable to modern economic challenges. Key supporting factors include the charismatic leadership of the caretaker, support from teachers and administrators, and collaboration with external partners. However, challenges such as low student awareness of entrepreneurship's importance and limited expertise in digital marketing were also identified. By integrating the values of Mau'idhotul Mukminin, Pesantren Fathul Ulum establishes an educational model relevant to globalization, equipping students with sharia-based economic skills while upholding moral values. This model is expected to serve as a reference for other Islamic boarding schools in developing entrepreneurship education.